(untitled) (Research, Society and Development, 2021)
The article discusses the role of the pedagogical coordinator in school management, bringing the issue: what is the role of the pedagogical coordinator and the impact on the school management process? The research has a qualitative approach, of the bibliographic type, and has as theoretical foundation the documents, decrees, resolutions and authors that discuss the topic discussed. The aim of the study is to understand the role of the pedagogical coordinator and the impact of their actions on the school management process. The research results show that the role of the pedagogical coordinator began to take shape in the 1980s, with the Promulgation of the Federal Constitution, which emphasizes democratic management, decentralization of power and decision-making, about educational aspects. It was only in 1996, with the enactment of the Law of Guidelines and Bases of Education, nº 9394/96, that the figure of the pedagogical coordinator emerged, as a specialist in education, as an articulator and mobilizer of all pedagogical processes that take place in everyday school life. This reflection and discussion on the role of this professional has been advocated nowadays, above all, based on resolutions and decrees promulgated by federal agencies.